2020
DOI: 10.1016/j.jallcom.2019.153448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of planetary ball milling on AlCoCrFeNi high entropy alloys prepared by Spark Plasma Sintering: Experiments and molecular dynamics study

Abstract: The elaboration of High Entropy Alloys (HEA) was investigated by means of powder metallurgy. We studied the combination of mechanical activation and reactive sintering in the case of AlCoCrFeNi. Elemental metallic powders were first processed by planetary ball milling over a long duration (28 h). The ratio K between the rotating speed of the sun wheel and the relative rotating speed of the grinding vials was set at 0.2 and 1 corresponding to "medium" energy milling. Given the particular hardness of chromium as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Therefore, the EAM potential developed by Farkas et al 66 is adopted for describing the interatomic interaction between Al–Cr–Co–Fe–Ni in the present study, which is consistent with the interaction of atoms in alloys that have been demonstrated in many previous studies 41 , 48 , 67 . The interaction force between the sample and the punch is assisted by Lennard–Jones (LJ) potential 32 , 64 .…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, the EAM potential developed by Farkas et al 66 is adopted for describing the interatomic interaction between Al–Cr–Co–Fe–Ni in the present study, which is consistent with the interaction of atoms in alloys that have been demonstrated in many previous studies 41 , 48 , 67 . The interaction force between the sample and the punch is assisted by Lennard–Jones (LJ) potential 32 , 64 .…”
Section: Methodssupporting
confidence: 82%
“…The model size of 200 Å × 55 Å × 110 Å (L × W × H) containing between 113,088 and 114,601 atoms is generated to study the deformation behavior of FCC Al x CoCrFeNi HEAs with various crystal structures during the nanoimprinting process. The lattice constant of the FCC phase is 3.525 Å, which obtains from previous studies 41 , 42 . The punch in the diamond lattice structure consists of about 57,888 atoms, and it is loaded along the Z direction.…”
Section: Resultssupporting
confidence: 60%
“…The peculiar state of the milled powders is the specificity of the mechanical activation process. Comprehensive characterization of the powder is reported elsewhere [28].…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the TCNI9 database predicts a greater amount FCC than the TCHEA3 database (see [28] for instance). The main difference between the two databases is that the TCHEA3 database was mainly developed for equimolar and near equimolar solid solutions.…”
Section: Oxygen Contaminationmentioning
confidence: 99%
See 1 more Smart Citation